Growth, mortality and migratory pattern of white shrimp (Litopenaeus vannamei, Crustacea, Penaeidae) in the Carretas-Pereyra coastal lagoon system, Mexico - Rivera Velásquez, G. (2008)
The growth, mortality and migration pattern of the population of Litopenaeus vannamei Boone 1931 in the Carretas-Pereyra coastal lagoon system, Mexico, were studied. The shrimp spatial distribution and abundance were analyzed in relation to salinity, water temperature, and substrate. A total of 2 669 shrimps was collected at 22 sites sampled monthly from March 2004 to August 2005. Juvenile shrimps of L. vannamei were present in the coastal lagoon system throughout the year, reaching densities from 0.001 to 0.302 ind/m2. The estimated daily growth rate was 0.06 to 0.27 mm carapace length (CL). No significant seasonal differences were appreciated. Weekly total mortality (Z) was between 0.04 and 0.34. Recruits, juveniles and sub-adults displayed a bimodal distributional pattern regulated by the prevailing conditions during the dry season. The peak abundance of juvenile stages occurred in December-January and March-May. The abundance presented an inverse correlation with salinity (r=-0.42; p < 0.05) and a positive correlation (r=0.44; p < 0.05) with silt content. No clear correlation was distinguished for emigration size with season of the year or water temperature.